Process Capability Model Based on COBIT 5 Assessments (Case Study) - Johanes Fernandes Andry (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
XYZ Company is Information and Communication Technology solutions provider in Jakarta. Started in 2003 as reseller product IT and development software customized, networking and other outsourcing project base. It has become imperative to strengthen IT governance and audit processes, to ensure the integrity of information systems. COBIT helps business and their IT achieves these, and builds a powerful, integrated framework for IT governance, control and audit processes. COBIT 5 is not only a cost-efficient approach, but also a conceptually easy framework for auditors to understand and communicate to the management. COBIT 5 moves away from the